Respostas
respondido por:
14
BC=(-1,-1,-4) e AC=(0,-2,-2)
AD=(-1,-1,-4) x (0,-2,-2)
AD=(0,2,8)
D=A+AD
D=(2,1,-1)+(0,2,8)
D=(2,3,7)
AD=(-1,-1,-4) x (0,-2,-2)
AD=(0,2,8)
D=A+AD
D=(2,1,-1)+(0,2,8)
D=(2,3,7)
lari03:
Obrigada, mas o resultado está errado.
respondido por:
131
temos que
BC x AC = produto vetorial entre os vetores
temos então
resolvendo
:::::::::::::::::::::::::::::::::::::::::::::::::
:::::::::::::::::::::::::::::::::::::::::::::::::::
então
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás